Trapping phenomena and degradation mechanisms in GaN-based power HEMTs. (May 2018) - Meneghini, Matteo; Tajalli, Alaleh; Moens, Peter; Banerjee, Abhishek; Zanoni, Enrico; Meneghesso, Gaudenzio
Abstract: This paper reports an overview of the most relevant trapping and degradation mechanisms that limit the performance and lifetime of GaN-based transistors for application in power electronics. Results obtained on state-of-the-art devices are described and discussed throughout the paper, with the aim of providing a clear description of the topic. The first part of the paper deals with the issue of dynamic-Ron : after describing a robust test strategy for the analysis of the pulsed characteristics of the devices, we discuss the voltage- and temperature-dependent pulsed I-V characteristics of 650 V-rated transistors, and the physical origin of dynamic Ron in these devices. The results demonstrate that through proper buffer optimization it is possible to reach negligible trapping at high voltage. The properties of the traps responsible for dynamic-Ron are also discussed in detail in the paper, based on drain-current transient data. A specific discussion is devoted to hot-electron trapping processes, that – under hard switching conditions – may lead to significant modifications in the resistance of the 2DEG. The second part of the paper deals with device degradation: based on a wide set of experimental results, we describe the physical mechanisms responsible for the worsening of the properties of the devices. More specifically, we demonstrate that stress in off-state conditions may result in measurable changes in the pinch-off voltage, mostly consisting in a negative-threshold instability (NBTI). The origin of this shift is discussed in detail; we also demonstrate that in a real-life cascode configuration (where a low, subthreshold leakage current flows through the device in the off-state), NBTI effects are mitigated. Finally, we discuss the stability of the gate-stack, induced by the exposure to positive gate bias.